2020
DOI: 10.2147/dmso.s280084
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identification of Reactive Hypoglycemia with Different Basic BMI and Its Causes by Prolonged Oral Glucose Tolerance Test</p>

Abstract: Purpose: To identify the population susceptible to reactive hypoglycemia and explain the possible reasons for their susceptibility. Methods: Ninety-four patients were divided into normal weight, overweight and obese groups before a 75-gram prolonged oral glucose tolerance test (POGTT). The incidence of reactive hypoglycemia (blood glucose ≤3.1 mmol/L or 55 mg/dL at points of 0-4 hours) was compared among three groups, and blood glucose and insulin levels were monitored simultaneously from 0-4 hours to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Previous studies which have analyzed RH occurrence based on OGTT were conducted in the heterogeneous population. Those investigations involved the following: patients in various age groups and BMI range [ 22 ], healthy subjects [ 12 ], pregnant women [ 23 ], and patients with a variety of medical conditions [ 24 , 25 , 26 ]. The results obtained in those studies are consistent with our results and confirmed relatively low frequency rate of hypoglycemia occurrence during OGTT.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies which have analyzed RH occurrence based on OGTT were conducted in the heterogeneous population. Those investigations involved the following: patients in various age groups and BMI range [ 22 ], healthy subjects [ 12 ], pregnant women [ 23 ], and patients with a variety of medical conditions [ 24 , 25 , 26 ]. The results obtained in those studies are consistent with our results and confirmed relatively low frequency rate of hypoglycemia occurrence during OGTT.…”
Section: Discussionmentioning
confidence: 99%
“…Postprandial hypoglycaemia is not uncommon, both in the general population and in those with diseases that alter the glucose metabolism. Table 1 reports some significant studies on the incidence of postprandial hypoglycaemia and shows that a 2-h OGTT does not suffice to fully understand the real prevalence of those suffering from postprandial hypoglycaemia, but that a 4-or 5-hour (OGTT) may be required [167,132,157].…”
Section: The Role Of Postprandial (Or Reactive) Hypoglycaemia In Epis...mentioning
confidence: 99%
“…It may be speculated that the relatively high risk of hypoglycaemia‐related events in the control group may partly reflect reactive hypoglycaemia due to prediabetes. A recent study, based on prolonged oral glucose tolerance testing, reported such a phenomenon, and also found the association to be stronger in persons with obesity 34 . In comparison, patients with baseline type 2 diabetes (or incident diabetes during follow‐up) will be at higher risk of hypoglycaemia, especially when treated with insulin or insulin secretagogues.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study, based on prolonged oral glucose tolerance testing, reported such a phenomenon, and also found the association to be stronger in persons with obesity. 34 In comparison, patients with baseline type 2 diabetes (or incident diabetes during follow-up) will be at higher risk of hypoglycaemia, especially when treated with insulin or insulin secretagogues. However, previous reports suggest that risk of hypoglycaemia in patients with diabetes is not increased by bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%